Field induced spin freezing and low temperature heat capacity of disordered pyrochlore oxide Ho2Zr2O7. (15th June 2022) - Sheetal,; Elghandour, A; Klingeler, R; Yadav, C S
Abstract: Spin ice materials are the model systems that have a zero-point entropy as T → 0 K, owing to the frozen disordered states. Here, we chemically alter the well-known spin ice Ho2 Ti2 O7 by replacing Ti sites with isovalent but larger Zr ion. Unlike the Ho2 Ti2 O7 which is a pyrochlore material, Ho2 Zr2 O7 crystallizes in disordered pyrochlore structure. We have performed detailed structural, ac magnetic susceptibility and heat capacity studies on Ho2 Zr2 O7 to investigate the interplay of structural disorder and frustrated interactions. The zero-field ground state exhibits large magnetic susceptibility and remains dynamic down to 300 mK without showing Pauling's residual entropy. The dynamic state is suppressed continuously with the magnetic field and freezing transition evolves (∼10 K) at a field of ∼10 kOe. These results suggest that the alteration of chemical order and local strain in Ho2 Ti2 O7 prevents the development of spin ice state and provides a new material to study the geometrical frustration based on the structure.